Cross talk between cellular redox state and the antiapoptotic protein Bcl-2 - Pohl, Sebastian; Agostino, Mark; Dharmarajan, Arunasalam; Pervaiz, Shazib (Mary Ann Liebert, Inc. Publishers, 2018)
SIGNIFICANCE B cell lymphoma-2 (Bcl-2) is the prototypical anti-apoptotic member of the Bcl-2 family that comprises proteins with contrasting effects on cell fate. Identified as a consequence chromosomal translocation (t 14:18) in human lymphoma, subsequent studies have revealed mutations and/or copy number alterations, as well as post-translational modifications, of Bcl-2 in a variety of cancers. The canonical function of Bcl-2 is linked to its ability to inhibit mitochondrial membrane permeabilization, regulating apoptosome assembly and activation by blocking cytosolic translocation of death amplification factors. RECENT ADVANCES Aside from maintaining mitochondrial integrity, a novel facet of Bcl-2 biology involves crosstalk with cellular redox state. Bcl-2 overexpression modulates mitochondrial redox metabolism to create a 'pro-oxidant' milieu, conducive for cell survival. Under oxidative stress, Bcl-2 functions as a redox sink to prevent excessive build-up of reactive oxygen species, inhibiting execution signals. Evidence indicates various redox-dependent transcriptional changes and post-translational modifications with different functional outcomes. CRITICAL ISSUES Understanding the complex interplay between Bcl-2 and the cellular redox milieu from the standpoint of cell fate signaling remains vital for understanding pathological states associated with altered redox metabolism and/or aberrant Bcl-2 expression. FUTURE DIRECTIONS Small molecule inhibitors of Bcl-2 are showing promise in the clinic. The non-canonical activity linked to cellular redox metabolism provides a novel avenue for the design and development of diagnostic and therapeutic strategies against cancers refractory to conventional chemotherapy.